Potential impact of dolphin watching unregulated activities in Patagonia - Coscarella, Mariano Alberto (2003)
Since 1997, dolphin watching activities have increased in Patagonia, with dusky and Commerson´s dolphins as the target species. To assess the impact of this activity, dolphin watching tours were monitored. For dusky dolphins, the number of tourists increased from 1,393 in 1997 to 1,840 in 2000. The encounter rate grew from 25% during 1999 to 90% in 2001. Most of the groups observed ranged from 50-100 animals. Data were recorded from both a commercial and a research boat. Dusky dolphins showed a short-term reaction to boats and feeding was the most affected behaviour. For Commerson´s dolphins, the number of tourists increased from 532 in 1999 to 2,113 in 2001. The encounter rate averaged 95.58%. There is seasonality in the abundance of Commerson´s dolphins in the area during the colder months (May-December) when schools are larger than in the warmer months. Dolphins showed a short-term reaction to the presence of the boat, performing aerial displays which are otherwise rarely seen. The direct gross estimated income for the companies carrying out dolphin watching is around US$60,000 per year. The activity has great potential to become an industry of its own.